Impact of a theoretically based sex education programme (SHARE) delivered by teachers on NHS registered conceptions and terminations: final results of cluster randomised trial. Issue 7585 (21st November 2006) - Henderson, M; Wight, D; Raab, G M; Abraham, C; Parkes, A; Scott, S; Hart, G
Abstract : Objective To assess the impact of a theoretically based sex education programme (SHARE) delivered by teachers compared with conventional education in terms of conceptions and terminations registered by the NHS. Design Follow-up of cluster randomised trial 4.5 years after intervention. Setting NHS records of women who had attended 25 secondary schools in east Scotland. Participants 4196 women (99.5% of those eligible). Intervention SHARE programme (intervention group) v existing sex education (control group). Main outcome measure NHS recorded conceptions and terminations for the achieved sample linked at age 20. Results In an "intention to treat" analysis there were no significant differences between the groups in registered conceptions per 1000 pupils (300 SHARE v 274 control; difference 26, 95% confidence interval −33 to 86) and terminations per 1000 pupils (127 v 112; difference 15, −13 to 42) between ages 16 and 20. Conclusions This specially designed sex education programme did not reduce conceptions or terminations by age 20 compared with conventional provision. The lack of effect was not due to quality of delivery. Enhancing teacher led school sex education beyond conventional provision in eastern Scotland is unlikely to reduce terminations in teenagers. Trial registration ISRCTN48719575 .